Optimizing of Integrated Port Infrastructure Design to Improve Maritime Logistics Efficiency in Eastern Indonesia - Rafli Yunianto Pratama (Journal of Maritime Policy Science, 2025)
Efficient port infrastructure is essential for reducing maritime logistics costs and strengthening inter-island connectivity in Eastern Indonesia, where many ports still face constraints such as insufficient basin depth, inefficient berth geometry, and breakwater systems that are not fully aligned with local oceanographic conditions. This study investigates how optimizing an integrated port-infrastructure design can improve maritime logistics efficiency and lower sea-transport costs by focusing on three technical components: modern-ship-compatible berth design, optimal harbor basin depth, and effective breakwater planning. A mixed-method approach was employed, combining a systematic review of recent scientific publications (2023–2024), technical design assessment against relevant international recommendations, and multi-site case studies supported by semi-structured interviews and operational document analysis. Results indicate that increasing basin depth from 10.5 m to 14 m can raise vessel carrying capacity by up to 35% and reduce regional logistics costs by approximately 22–28%. Optimizing berth dimensions to a 600–800 m effective length and 50–65 m operational width can improve cargo handling efficiency by up to 40%, while a site-adapted rubble-mound breakwater can cut weather-related operational downtime by about 15–20%. These findings demonstrate that strategically integrated design optimization can substantially enhance port throughput, reliability, and cost competitiveness in Eastern Indonesia; therefore, prioritizing targeted infrastructure investment, adopting fit-for-purpose international design standards, and strengthening digital port management are recommended to accelerate regional economic connectivity.